THE PERSONALIZATION EFFECT: HOW CONTENT CUSTOMIZATION SHAPES CUSTOMER SATISFACTION AND BRAND LOYALTY AMONG NETFLIX SUBSCRIBERS IN JABODETABEK - Rafly Raihan Ardyansyah (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the influence of content personalization on consumer satisfaction and brand loyalty of Netflix users in Jabodetabek and to examine the mediating role of consumer satisfaction. A quantitative method with purposive sampling was used on 100 active Netflix users. Data was collected through a Google Forms questionnaire with a Likert scale and analyzed using PLS-SEM with SmartPLS 3.29. The research findings support the first hypothesis, which states that content personalization influences consumer satisfaction. The second hypothesis indicates that content personalization affects brand loyalty. The third hypothesis proves that consumer satisfaction influences brand loyalty. Additionally, the fourth hypothesis confirms that consumer satisfaction mediates the relationship between content personalization and brand loyalty. This result confirms that content personalization, via Netflix's recommendation algorithm, plays a significant role in increasing consumer satisfaction and loyalty in the Indonesian market.